2005
DOI: 10.1136/aim.23.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the Treatment of Post Viral Fatigue Syndrome – a Case Report

Abstract: This case report concerns the treatment of post viral fatigue (chronic fatigue syndrome) with electroacupuncture. This condition is particularly difficult to treat whether using conventional or complementary therapy. Whilst the treatment did not cure the patient, it appears to have facilitated her return to work and markedly improved her symptoms. There are few publications on acupuncture treatment of this condition and the approach used here has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Anti-depressants, NSAIDs, anxiolytic drugs, stimulants, anti-allergy drugs and anti-hypotensive drugs have all been used, but are not universally beneficial [26]. The lack of effective therapy has led to use of plant extracts [27], homeopathy [28], [29], hypnosis [30], acupuncture [31], and whole body periodic acceleration stress [32], none with sustained benefits. The only modalities of treatment that have any proven benefits are cognitive behavioral therapy and graded exercise programs, both of which appear to aid by improving coping skills rather than reduce symptoms [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-depressants, NSAIDs, anxiolytic drugs, stimulants, anti-allergy drugs and anti-hypotensive drugs have all been used, but are not universally beneficial [26]. The lack of effective therapy has led to use of plant extracts [27], homeopathy [28], [29], hypnosis [30], acupuncture [31], and whole body periodic acceleration stress [32], none with sustained benefits. The only modalities of treatment that have any proven benefits are cognitive behavioral therapy and graded exercise programs, both of which appear to aid by improving coping skills rather than reduce symptoms [33].…”
Section: Discussionmentioning
confidence: 99%
“…If XMRV infection parallels other retroviral infections, then the use of combination antiretroviral therapy might maintain XMRV suppression, prevent the emergence of resistance to antiretroviral agents and possibly also cause amelioration of disease. For HIV-1, combination therapy works especially well when the combined drugs have different viral protein targets, or in the case of nucleosides, utilize different kinases for their activation to NTP analogs [31]. We, therefore, judiciously selected drug combinations that inhibit XMRV, such as RAL with ZDV or TDF or L-000870812.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of conventional therapies to provide adequate relief from the symptoms of CFS has led sufferers to experiment with various alternative therapies with markedly differing outcomes (Tharakan and Manyam, 2006;Gregg, 1997;Sekiya et al, 2005;Mears, 2005;Sackner et al, 2004;Weatherley-Jones et al, 2004;Ernst, 2004).…”
Section: Non-specific Therapiesmentioning
confidence: 97%
“…78 A case study of chronic fatigue syndrome reported by Mears in 2005 showed remarkable improvement after continuous treatment with acupuncture therapy for 6 months. 79 According to Lin et al, chronic fatigue syndrome subjects showed reduction in pain, ability to sleep better, increased energy levels, and decreased fatigue levels after treatment with acupuncture when compared with untreated subjects. 80 Many studies have used traditional Chinese herbal medicines to treat chronic fatigue syndrome.…”
Section: Effectiveness Of Complementary and Alternative Therapies In mentioning
confidence: 99%